Demographic Shifts and their Consequences for the Investment Funds in the EU - Kasnauskienė, Gindra; Michnevič, Karol (Ekonomika, 2015)
Solid theoretical reasons exist for the link between demographics and various economic, financial and social indicators. The aim of this article is to assess the influence of demographic shifts on investment fund flows in the EU from 1996 to 2013. In order to achieve this aim, a fixed effects model is constructed via panel regression and used to test the hypothesis as well as to derive conclusions. The authors hypothesise the presence of a statistically significant non-linear effect of demographic age shares on investment fund flows. The results are juxtaposed with a prior comparable research. This article is expected to benefit the financial sector and to provide guidance to market regulators.